Curriculum Materials, Themes and Teachers' Conceptions in Science Education in the Early Years of Elementary School - Adriana Klem Mendonça; Maria Cristina Ferreira dos Santos (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The study deals with topics and curriculum materials developed and/or used by teachers in science education and is supported by theoretical contributions from the field of curriculum and science education. The objective was to analyze curriculum materials developed and/or used by teachers in the early years of elementary school in a municipal public school in Itaboraí, Rio de Janeiro. The research had a qualitative nature and semi-structured interviews were carried out with five teachers who taught in the initial years in 2020 and 2021. They affirmed that they used the Science Curriculum Framework of Itaboraí in the planning and development of activities and didactic materials that addressed the environment, human beings and health, and technological resources. The analysis indicated curricular re-elaborations for the pandemic context, adaptations, and elements of knowledge didactics for the early years in science education, highlighting the role of teachers in the production of the science curriculum at school.